Pengaruh Investasi, Human Capital, Kesenjangan Sosial, dan Pertumbuhan Ekonomi terhadap Kesempatan Kerja di Pulau Sumatera - Harahap, Siti Holijah; Rujiam, Rujiam; Syafii, M (Ekonomis: Journal of Economics and Business, 2024)
This research aims to examine the influence of investment, human capital, social inequality and economic development on job prospects on the island of Sumatra. Associative quantitative research is used as an investigative approach. Secondary statistical data originating from the Central Statistics Agency (BPS) includes information regarding investment, human development index, Gross Regional Domestic Product (GRDP), Gini index, and job opportunity levels from 2018 to 2022. The results of this research show that simultaneously and partial investment factors, human capital, socio-economic disparities have a positive influence on employment opportunities on the island of Sumatra. Investment, human capital, social inequality and economic growth contribute 86.9% to the variation in employment opportunities.